2016
DOI: 10.1038/srep36441
|View full text |Cite
|
Sign up to set email alerts
|

The prion protein family member Shadoo induces spontaneous ionic currents in cultured cells

Abstract: Some mutant forms of the cellular prion protein (PrPC) carrying artificial deletions or point mutations associated with familial human prion diseases are capable of inducing spontaneous ionic currents across the cell membrane, conferring hypersensitivity to certain antibiotics to a wide range of cultured cells and primary cerebellar granular neurons (CGNs). These effects are abrogated when the wild type (WT) form is co-expressed, suggesting that they might be related to a physiological activity of PrPC. Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In addition, studies by our group demonstrated that, contrary to wild type PrP C , Sho expression sensitizes human SH-SY5Y and HEK293 cells to certain drugs, similar to the toxic, central region (CR)-deletion mutant, ∆ , PrP∆CR-a phenotype that could be rescued by the wild type PrP C [63]. Additionally, we showed that the expression of Sho produces spontaneous large inward currents in cell cultures, a similar effect that is exerted by the HD-deletion mutant PrP∆HD [64], which could also be rescued by PrP C in both cases. In animal models, Sho and PrP are observed to be involved in embryonic development; however, a cross regulation between the levels of the two proteins is not apparent in the adult state [47].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, studies by our group demonstrated that, contrary to wild type PrP C , Sho expression sensitizes human SH-SY5Y and HEK293 cells to certain drugs, similar to the toxic, central region (CR)-deletion mutant, ∆ , PrP∆CR-a phenotype that could be rescued by the wild type PrP C [63]. Additionally, we showed that the expression of Sho produces spontaneous large inward currents in cell cultures, a similar effect that is exerted by the HD-deletion mutant PrP∆HD [64], which could also be rescued by PrP C in both cases. In animal models, Sho and PrP are observed to be involved in embryonic development; however, a cross regulation between the levels of the two proteins is not apparent in the adult state [47].…”
Section: Introductionmentioning
confidence: 75%
“…In the case of Sho, two bands appear at around the expected weight of Sho-EYFP (~45-49 kDa), recognized by both α-Sho and α-GFP antibodies in Sho-EYFP cells, which are absent in parental N2a cell samples (Figure 2B, lanes 1-2 and 4-5). It should be noted that there are no unequivocally good anti-Shadoo antibodies available and that cross-reactive bands are frequently apparent on blots of various cells by anti-Sho antibodies [47,60,63,64,82]. However, since α-GFP shows similar bands, these might be two forms of Sho.…”
Section: Resultsmentioning
confidence: 99%
“…The recently proposed channel activity of Sho 41 , which is also characteristic to some pathogenic PrP mutants, may be linked to a physiological function of Sho.…”
Section: Discussionmentioning
confidence: 98%
“…These cells are well characterized and broadly used as a cellular model system in the study of physiology of cellular and the pathological prion protein 90,156 . N2a cells possess detectable amounts of endogenous PrP but not Sho; at least the endogenous Shadoo expression cannot be detected in these cells with the currently available shadoo antibodies 70,86,96,97,157 . To compare Sho and PrP, we generated N2a cells stably expressing either Sho or PrP in fusion with a fluorescent protein (EYFP for Sho and EGFP for PrP) tag by using the plasmid constructs described in the Materials and methods section for PrP (for the plasmid Map see Appendix-I, Figure A1) and earlier by our group for Sho 69 .…”
Section: N2a Stable Transgenic Cells Developed For the Studies And Th...mentioning
confidence: 99%
“…On the other hand, opposing roles for Sho and wild type PrP had also been reported: expression of Sho caused drug hypersensitivity in certain type of cells, while expression of wild-type PrP rescued cells against the effect of the same drugs 96 . Also, Sho induces large spontaneous ionic currents similarly to the toxic PrP mutant associated with familial human prion diseases, whereas expression of wild type PrP rescues the same cells against these effects 97 . Altogether, these demonstrate that while Sho and PrP may act similarly then may undertake opposing roles as well depending on the experimental setting and the process studied, and more data are required to understand their exact relation and interplay.…”
Section: Functional Similarities and Differences Between Sho And Prp Cmentioning
confidence: 99%